2016
DOI: 10.2147/rrfms.s93974
|View full text |Cite
|
Sign up to set email alerts
|

Post-mortem imaging in forensic investigations: current utility, limitations, and ongoing developments

Abstract: Forensic imaging is a new field with increasing application all over the world. However, its role in legal medicine is controversial, mostly due to the use of undefined and unclear terms. The aim of this article is to describe forensic imaging and to explain the various techniques that pertain to it. Essentially, these methods consist of radiological methods such as conventional radiography, computed tomography, and magnetic resonance imaging, but other techniques such as 3D surface scanning are also employed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…Access to such technology may vary depending on geographic regions as well. While postmortem virtual autopsies utilizing CT scans (sometimes referred to as virtopsies or postmortem CTs) are relatively common among European countries [ 73 ], their incorporation in the United States is lagging. In fact, a relatively recent article from 2018 indicated that only four U.S. agencies have CT equipment available for regular use [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Access to such technology may vary depending on geographic regions as well. While postmortem virtual autopsies utilizing CT scans (sometimes referred to as virtopsies or postmortem CTs) are relatively common among European countries [ 73 ], their incorporation in the United States is lagging. In fact, a relatively recent article from 2018 indicated that only four U.S. agencies have CT equipment available for regular use [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT acquisition was performed during operation of the pump. Currently, a multi-phase procedure is commonly used -multi-phase post mortem computed tomography angiography (MPCT), which includes a native CT scan prior to administration of the contrast agent, followed by contrast imaging in three angiographic phases: arterial, venous and dynamic (artificial circulation) (8). Comparing the data obtained in this manner with the results of medico-legal autopsies of 50 corpses, Chevallier et al (4) reported an increase in the diagnostic value of MPMCTA as compared to native CT from 65% to 80.9%, while conventional autopsies identified 83.1% of pathological lesions.…”
Section: Characterization Of Post-mortem Imagingmentioning
confidence: 99%
“…1). Nevertheless, their combined use unquestionably increases the effectiveness of autopsy diagnostics (8).…”
Section: Fig 3 Ct Scan Of Head Of a Dog Shot With A Shotgun Bulletmentioning
confidence: 99%
“…Before LiDAR, 3D documentation was time consuming and expensive [ 11 ]. Besides, usually it requires specific skills, for example, good photographic expertise or specific professional training, particularly in the case of CT 3D reconstruction [ 11 , 12 ]. Moreover, the equipment required for 3D documentation is not present in every facility (e.g., the 3D system “VirtoScan-on-Rails”, used by Kottner et al) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%